Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Sure, let's solve the given mathematical expression step-by-step. The expression is:
[tex]\[ \frac{2}{4}+\frac{3}{6}+\left[\frac{4}{2}+\left\{\frac{2}{4}-\left(\frac{3}{4}+\frac{2}{4}\right)\right\}\right] \][/tex]
Let's break it down and solve it step by step:
1. Calculate individual fractions:
[tex]\[ \frac{2}{4} = 0.5 \][/tex]
[tex]\[ \frac{3}{6} = 0.5 \][/tex]
[tex]\[ \frac{4}{2} = 2.0 \][/tex]
[tex]\[ \frac{2}{4} = 0.5 \][/tex]
[tex]\[ \frac{3}{4} = 0.75 \][/tex]
[tex]\[ \frac{2}{4} = 0.5 \][/tex]
2. Calculate the innermost parentheses:
[tex]\[ \left(\frac{3}{4} + \frac{2}{4}\right) = 0.75 + 0.5 = 1.25 \][/tex]
3. Now, calculate the expression inside the curly brackets:
[tex]\[ \frac{2}{4} - 1.25 = 0.5 - 1.25 = -0.75 \][/tex]
4. Next, calculate the expression inside the square brackets:
[tex]\[ \frac{4}{2} + (-0.75) = 2.0 - 0.75 = 1.25 \][/tex]
5. Finally, sum all the results:
[tex]\[ \frac{2}{4} + \frac{3}{6} + \left(1.25\right) = 0.5 + 0.5 + 1.25 = 2.25 \][/tex]
So, the step-by-step solution for the expression [tex]\(\frac{2}{4}+\frac{3}{6}+\left[\frac{4}{2}+\left\{\frac{2}{4}-\left(\frac{3}{4}+\frac{2}{4}\right)\right\}\right]\)[/tex] is [tex]\(2.25\)[/tex].
[tex]\[ \frac{2}{4}+\frac{3}{6}+\left[\frac{4}{2}+\left\{\frac{2}{4}-\left(\frac{3}{4}+\frac{2}{4}\right)\right\}\right] \][/tex]
Let's break it down and solve it step by step:
1. Calculate individual fractions:
[tex]\[ \frac{2}{4} = 0.5 \][/tex]
[tex]\[ \frac{3}{6} = 0.5 \][/tex]
[tex]\[ \frac{4}{2} = 2.0 \][/tex]
[tex]\[ \frac{2}{4} = 0.5 \][/tex]
[tex]\[ \frac{3}{4} = 0.75 \][/tex]
[tex]\[ \frac{2}{4} = 0.5 \][/tex]
2. Calculate the innermost parentheses:
[tex]\[ \left(\frac{3}{4} + \frac{2}{4}\right) = 0.75 + 0.5 = 1.25 \][/tex]
3. Now, calculate the expression inside the curly brackets:
[tex]\[ \frac{2}{4} - 1.25 = 0.5 - 1.25 = -0.75 \][/tex]
4. Next, calculate the expression inside the square brackets:
[tex]\[ \frac{4}{2} + (-0.75) = 2.0 - 0.75 = 1.25 \][/tex]
5. Finally, sum all the results:
[tex]\[ \frac{2}{4} + \frac{3}{6} + \left(1.25\right) = 0.5 + 0.5 + 1.25 = 2.25 \][/tex]
So, the step-by-step solution for the expression [tex]\(\frac{2}{4}+\frac{3}{6}+\left[\frac{4}{2}+\left\{\frac{2}{4}-\left(\frac{3}{4}+\frac{2}{4}\right)\right\}\right]\)[/tex] is [tex]\(2.25\)[/tex].
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.